PEMBUATAN DAN EVALUASI GRANUL EFFERVESCENT VITAMIN C - Faidah, Anis; Na'imah, Janatun (JIFI (Jurnal Ilmiah Farmasi Imelda), 2024)
Vitamin C is a compound with the molecular formula and the chemical name 2-oxo-L-threo-hexono-1,4-lactone-2,3-enediol. Vitamin C can improve the immune system and as an antioxidant can prevent and treat infections and various other diseases, by fighting bacteria, viruses and fungal diseases. Vitamin C in the form of effervescent granules is an alternative to consuming vitamins for someone who has difficulty swallowing medication in tablets, pills or capsules. This research aims to determine the evaluation results of making vitamin C effervescent granules through several evaluations including determining the real specific gravity, compressible specific gravity, compressibility, and dispersion time tests for effervescent granules. The research method was experimental which was carried out at the Pharmacy Laboratory, Faculty of Health, Muhammadiyah University, Gresik. Based on the evaluation results, the real specific gravity was 0.58 g/mL, the compressible specific gravity was 0.67 g/mL, the compressibility was 13.4% and the dispersion time was ± 4.31 minutes. Based on these results, the vitamin C effervescent granule formula that has been made has very good flow properties as seen from the compressibility of the effervescent granules below 15%, and the granule dispersion time is in the good category because the time required is ? 5 minutes.